A Systematic Review of Purpose and Latency Effect in the Virtual Reality Environment - Anua, Muhammad Danish Affan; Ismail, Ismahafezi; Shapri, Nur Saadah Mohd; Amin, Maizan Mat; M. Arsad, Mohd Azhar (Intelligent Technologies for Interactive Entertainment, 2022)
VR means immersing oneself in a virtual environment where all we see is three dimensional (3D) computer-generated. VR has been around for several decades now, but in recent years, the consistency of experience has dramatically improved. This technology has been recognised worldwide, making the adoption of VR a more progressive widespread occurrence across various fields. VR technology evolves very fast and significant as it merges with artificial intelligence (AI), thus transforming the way people use machines and smartphones in daily life to communicate with the world around them. However, there is a problem commonly faced by the virtual reality user, which is cybersickness or motion sickness in the virtual reality environment. As the result, a systematic review has been made to gain a better understanding and present this information in the form of a written summary of current researches. The study of the previous research publication of review papers was limited around 2017 to 2021 from the Scopus library. Among 187 results, five of them were selected since they met the criteria through the inclusion and exclusion criteria procedure. Eight purposes were found and listed together with the outcomes. This paper also briefly discusses the latency effect and its relationship with motion sickness in the virtual reality environment and system. Understanding the purpose and latency effect in the virtual reality environment can encourage researchers and developers to find a better solution to counter the motion sickness problem.